PELAYANAN PUBLIK ADMINISTRASI KEPENDUDUKAN DALAM PEMBUATAN AKTA KELAHIRAN DI DESA AUR SAMPUK KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Asril Guwandi E.42009052 (FISIP Universitas Tanjungpura Pontianak, 2022)
This script intend to determine the quality of public services , especially the administration of the village population on the Aur Sampuk Village Sengah Temila District Landak Regency. This script also written to learn the phenomena of services performed by the village head and village officials to Sampuk Aur Villagers . The theory used as knives analysis in this study is a theory which states Zeithaml et al public service quality can be measured with 5 dimensions , namely : tangible, reliability, responsiviness, assurance, and empathy. Research using qualitative descriptive research paradigm thats the data collected in the form of words , images , and not the numbers . Location of the study are on the Office of Aur Sampuk Village Sengah Temila District Landak Regency. The subject is village head , village officials and Aur Sampuk village communities, data collection techniques with observation , interviews , documentation . This study resulted in the conclusion that the general population administration of public services has been implemented by the government Sampuk Aur village . Village Government in dimensions Aur Sampuk responsiviness and empathy have been responsive in responding to any request from the public service , public services performed by friendly and courteous . Village Community Aur Sampuk feel quite satisfied with the results of the services they receive from the village head and village officials Aur Sampuk . However, based on tangible dimensions , and the assurance that discipline Aur village government officials still lack discipline Sampuk this can be seen from the apparatus which rarely entered or skipped during business hours and village government officials Aur Sampuk technology stuttering so cooperate with the employers computer rentals .Keywords : Administration of Population, Public Service, village government officials Aur Sampuk, tangible , reliability , responsiviness , assurance, and empathy.